Dysbiosis in the Pathogenesis of Pediatric Inflammatory Bowel Diseases - Donatella Comito; Claudio Romano (International Journal of Inflammation)
Inflammatory bowel diseases (IBDs) are chronic inflammatory conditions of the gastrointestinal tract that occur in genetically susceptible individuals. Crohn’s disease (CD) and ulcerative colitis (UC) are two major types of IBD. In about 20–25% of patients, disease onset is during childhood and pediatric IBD can be considered the best model for studying immunopathogentic mechanisms. The fundamentals of IBD pathogenesis are considered a defective innate immunity and bacterial killing with overaggressive adaptive immune response. A condition of “dysbiosis”, with alterations of the gut microbial composition, is regarded as the basis of IBD pathogenesis. The human gastrointestinal (GI) microbial population is a complex, dynamic ecosystem and consists of up to one thousand different bacterial species. In healthy individuals, intestinal microbiota have a symbiotic relationship with the host organism and carry out important metabolic, “barrier,” and immune functions. Microbial dysbiosis in IBD with lack of beneficial bacteria, together with genetic predisposition, is the most relevant conditions in the pathogenesis of the pediatric IBD.